Binuclear Mn2+ complexes of a biphenyltetracarboxylic acid with variable N-donor ligands: syntheses, structures, and magnetic properties. Issue 13 (6th March 2018) - Su, Feng; Zhou, Cheng-Yong; Han, Chun; Wu, Lin-Tao; Wu, Xi; Sun, Long; Su, Jing; Feng, Si-Si; Lu, Li-Ping; Zhu, Miao-Li
Abstract : A series of manganese(ii ) coordination polymers show a variety of features due to the recognition and assembly processes of the N-donor ligands. Abstract : Four new manganese(ii ) metal–organic frameworks based on H4 bpta (H4 bpta = 3, 3′, 5, 5′-biphenyltetracarboxylic acid) and N-donor ligands, namely [Mn2 (4, 4′-bipy)(bpta)] n (1 ), [Mn2 (1, 4-bib)2 (bpta)] n ·2 n (H2 O·DMF) (2 ), [Mn2 (1, 3-bimb)2 (bpta)] n ·2 n H2 O (3 ), and [Mn2 (1, 4-bimb)2 (bpta)] n ·2 n H2 O (4 ) (4, 4′-bipy = 4, 4′-bipyridine, 1, 4-bib = 1, 4-bis(imidazol-1-yl)benzene, 1, 3-bimb = 1, 3-bis((1 H -imidazol-1-yl)methyl)benzene, and 1, 4-bimb = 1, 4-bis((1 H -imidazol-1-yl)methyl)benzene), have been obtained under solvothermal conditions. In these complexes, the fully deprotonated bpta 4− ligands link binuclear SBUs to construct 2D layers with (4, 4)-connected topologies. Complex1 is a 3D network with 1D zigzag chains built up from 4-connected bpta 4− ligands that contain carboxylate groups bridging Mn 2+ ions in a rather rare syn – syn geometry. Complex2 exhibits a 3D porous network with syn – anti bridging dimeric subunits. Complex3 is a (3, 4)-connected 2D novel network with double helix chains formed by cis -1, 3-bimb linkers. The structure of complex4 is similar to that of2, but it consists of tiny pores due to trans -1, 4-bimb linkers. Magnetic studies reveal that1 is perfectly fitted by the modified Fisher model to yield an effective intrachain antiferromagnetic coupling ( J = −2.21(1) cm −1 ). Complexes2–4 show antiferromagnetic interactions ( J = −1.57(2) cm −1 for2, and J = −0.68(2) cm −1 for3 ) in dimeric units of Mn2 (μ-COO)2 2+ related to double s yn – anti and syn – syn carboxylate bridges. An important repetitive feature of all these complexes with s yn – anti or syn – syn carboxylate bridges is that the antiferromagnetic coupling is very small. In addition, the gas sorption exploration of2 exhibits relatively high sorption of CO2 but very low sorption of N2, making it a promising material for CO2 /N2 separation.